# trigonometry

posted by .

tanx/2=tanx/secx+1

• trigonometry -

Is it
tan (x/2) = tanx/secx + 1 ??
tan (x/2) = tanx/(secx +1) ??
(tanx)/2 = tanx/secx + 1 ?? ---> the way you typed

are we solving the equation, or is it supposed to be an identity?

Can you see why brackets are essential?

## Similar Questions

1. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
2. ### Trigonometry

What are the steps in verifying that -ln|secx+tanx| = ln|secx-tanx| Thanks
3. ### Trigo

Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in terms of sinx and cosx. I don't know what i'm supposed to do, and i don't come to an answer! Help, thanks! my workings: tan(45+x)= (1+tanx)/(1-tanx) a/b = (1+tanx)/(1-tanx) …
4. ### Trigonometry

Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in terms of sinx and cosx. I don't know what i'm supposed to do, and i don't come to an answer! Help, thanks! my workings: tan(45+x)= (1+tanx)/(1-tanx) a/b = (1+tanx)/(1-tanx) …
5. ### precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a negatvie:( …
6. ### Math

I can't find the integral for (tanx)^(6)*(secx)^(2) I tried splitting up tanx into (tanx)^2*(tanx)^4 and let the latter equal (secx)^2 - 1. Please help, thanks!
7. ### Trig

Verify the identity. (secx + tanx)/(secx - tanx) = (1 + 2sinx + sin(^2)x)/cos(^2)x
8. ### Trigonometry

Can you please help me verify these? >sin7x-sin5x= tanx(cos7x-cos5x) >(1-cosx)cot(1/2x) = sinx >1+tanx tan(x/2) = secx Its very confusing because of all the double-half angle formulas >_<
9. ### maths

npr=3024 find r (2)dy/dx=secx-tanx/secx+tanx. plz help
10. ### Math

How do i get left side to equal rs? (Tanx/1+secx)+(1+secx/tanx)=(2/sinx)

More Similar Questions

Post a New Question